REVITALISASI PERAN PESANTREN DI ERA 4.0 - Mohammad Darwis (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2020)
This paper discusses the revitalization of the role of pesantren in the 4.0 era by critically examining the process of change and development of pesantren due to the industrial revolution 4.0. This study begins with the development of an era that is entering the 4.0 revolution era, where all life is done digitally, starting from the digital economy, artificial intelligence, big data, and robotic. This will further change the established pesantren curriculum system, and in this era the world of education will experience its own challenges to adjust it including the education found in pesantren. Therefore pesantren must be able to make a change by revitalizing the role of pesantren so that later the existence of pesantren in the community can continue to be maintained, and pesantren graduates will be able to compete when in the community.